A Socio-Historical Mapping of Translation Fields: A Case Study of English Self-Help Literature in Arabic Translation - Alqarni Abdullah; Altalidi Bandar; Sahari Yousef (Open Cultural Studies)
This study advances the application of Pierre Bourdieu’s social field as a heuristic conceptual tool in the context of translation studies, offering a methodological framework that integrates socio-historical analysis with bibliographical research. By exploring the field of Arabic translations of English self-help literature in the Kingdom of Saudi Arabia (KSA) between 1982 and 2016, the article illustrates how Bourdieu’s conceptualisation of social fields can be operationalised to define the boundaries, agents, production, and practices within a translation field. A bespoke bibliographical database comprising 993 translated self-help titles was constructed to provide a detailed mapping of the field’s historical trajectory and production dynamics. Through this integration of theory and empirical data, the study demonstrates how field theory can enrich the analysis of translation as a social practice, revealing the interactions between translation agents and the socio-historical forces that shape the production of translations. The findings suggest that this integrated approach can serve as a heuristic model for the socio-historical analysis of translation fields across different language pairs, temporal periods, and geographic contexts, contributing to future research in translation sociology and translation bibliographies.